Cloud based Heartbeat Rate Monitoring System with Location Tracking - Malathy, Batumalay*; Hong, Shu Ming; Deshinta, Arrova Dewi* (INTI International University, 2020)
Heartbeat rate reflects an individual’s physical health and the status of a person cardiovascular health. A person with poor cardiovascular health is subjected to various heart diseases including heart attack. Heart attack is one of the deadliest diseases worldwide and the number one cause of death annually. People with poor cardiovascular health are required to be monitored in order to prevent a life-threatening situation. To help on this issue, we proposed a monitoring system through cloud servers to monitor people with poor cardiovascular health constantly. This system is developed using a lightweight Bluetooth ECG sensor, Android Technology, Web application as well as cloud services provided by Firebase. This system is portable, allowing patient to carry it on a travel. The heartbeat rate monitoring system with enhanced feature of alerting and notifying user through cloud servers. The firebase realtime database allow data to be transferred in realtime and user can send an alert through a push button. The proposed system allows patient to be monitored and alert users in case of any emergencies. A location tracking is also included as an added value feature. This may help in life threatening situations that will endanger patient’s life. In addition, cloud database is able to store and monitor data constantly to review patient’s heart condition.